Effects of increased CO2 concentration on nutrient limited coastal summer plankton depend on temperature. (4th February 2016) - Paul, Carolin; Sommer, Ulrich; Garzke, Jessica; Moustaka‐Gouni, Maria; Paul, Allanah; Matthiessen, Birte
Abstract: Increasing seawater temperature and CO2 concentrations both are expected to increase coastal phytoplankton biomass and carbon to nutrient ratios in nutrient limited seasonally stratified summer conditions. This is because temperature enhances phytoplankton growth while grazing is suggested to be reduced during such bottom‐up controlled situations. In addition, enhanced CO2 concentrations potentially favor phytoplankton species, that otherwise depend on costly carbon concentrating mechanisms (CCM). The trophic consequences for consumers under such conditions, however, remain little understood. We set out to experimentally explore the combined effects of increasing temperature and CO2 concentration for phytoplankton biomass and stoichiometry and the consequences for trophic transfer (here for copepods) on a natural nutrient limited Baltic Sea summer plankton community. The results show, that warming effects were translated to the next trophic level by switching the system from a bottom‐up controlled to a mainly top‐down controlled one. This was reflected in significantly down‐grazed phytoplankton and increased zooplankton abundance in the warm temperature treatment (22.5°C). Additionally, at low temperature (16.5°C) rising CO2 concentrations significantly increased phytoplankton biomass. The latter effect however, was due to direct negative impact of CO2 on copepod nauplii which released phytoplankton from grazing in the cold but not in the warm treatments. Our results suggest that future seawater warming has the potential to switch trophic relations between phytoplankton and their grazers under nutrient limited conditions with the consequence of potentially disguising CO2 effects on coastal phytoplankton biomass.